Componentes de produção da Heliconia golden torch (Heliconia psittacorum x Helinonia spathocircinada) influenciados pela adubação mineral e orgânica - Farias, Alonso Pereira de (2004)
The association of chemical fertilizer with organic fertilizer is an application following to several farmers of tropical flowers, especially in Alagoas state, to have better results in productivity and quality of produced flowers and leaves. The present study has aimed to evaluate the components of Golden Torch (H. psittacorum x H. spathocircinada), when submitted to several types of fertilization. The experiment was conducted in area that belongs the Escola Agrotécnica Federal, at Satuba-Alagoas (Brazil). The experimental design was randomized blocks with 5 replications and 10 treatments to know: T1) TEST, without fertilization; T2) Mineral fertilizer (AM); T3) Cow manure (EG); T4) Chicken bedding (CF); T5) Filter tart (TF); T6) urban garbage compound (CLU); T7) Cow manure + Mineral fertilizer (EG + AM); T8) Chicken bedding + Mineral fertilizer (CF + AM); T9) Filter tart + Mineral fertilizer (TF+AM); T10) urban garbage compound + Mineral fertilizer (CLU+AM). The following variables (components of production): number of the sprouts by rhizome (NPt), the beginning of the flowering (IF), number of the stem flower by rhizome (NHf), length of the stem flower (CHf), diameter of the stem flower (DHf), length of the bract (CB), interval of the flowering (Inf), number of the leaves by stem flower (NFh) and leaf area by stem flower (AFh) were studied. It was verified that: the fertilized treatments overtaken statistically not fertilized treatments in every studied variables; the combinations of organic fertilizer and mineral fertilizer (mineral organic) caused significant increment in indices of production, when compared with fonts of organic fertilizer, there wasn t significant statistic difference between treatments with organic fertilizer in components of production of H. Golden Torch; the fonts of organic fertilizer associated with mineral fertilizer (mineral organic) haven t showed significant statistic difference, between them, in studied components of production and, it was also verified that the production of the number of sprouts by rhizome and, the same way, the production of the length of the stem flower have influenced directly in the productivity of the number of the stem flower.